Historical Origin and Usage of Clause of Reason in English (Czech Journal of Multidisciplinary Innovations, 2022)
This article considers the origin of clause of reason in English. Deeply was studied works of linguist's and were done analysis of complex sentences on the basis of literary works of authors such as: Jane Austin’s novel Pride and Prejudice, Charlotte Bronte’s Jane Eyre.